Advances in management accounting. vol. 34 - Akroyd, Chris (Associate professor of accounting) (Advances in management accounting ;, 2023)
Volume 34 of Advances in Management Accounting uses a variety of methods, from experiments to surveys, to build upon existing knowledge within the management accounting discipline. Containing a diverse range of authors from Australia, China, Germany, New Zealand, Singapore, South Africa, the United Kingdom and the United States of America, this theoretically sound and practical research has a cutting-edge, wide-reaching appeal. Showcasing chapters on performance measurement, management control, incentive compensation and budgeting, this edited collection appeals particularly to management accountants in practice, analysing topics such as the effects that narcissism, psychological pressure, honesty, fairness, service quality and corporate social responsibility have on both performance and the roles of management accountants. Advances in Management Accounting (AMA) publishes thought-provoking volumes that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. The series seeks thoughtful, well -developed articles on a variety of current topics in management accounting, broadly defined. All research methods including survey research, field tests, corporate case studies, experiments, meta-analyses, and modeling are welcome.